Mental practice maintains range of motion despite forearm immobilization: a pilot study in healthy persons - Frenkel, Marie Ottilie; Herzig, Daniela Sarah; Gebhard, Florian; Mayer, Jan; Becker, Clemens; Einsiedel, Thomas (Journal of rehabilitation medicine, 2014)
Objective: To determine whether mental practice of wrist movements during forearm immobilization mai...